2019
DOI: 10.21448/ijsm.629151
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Green Extraction of Caffeine and Catechins from Green Tea

Abstract: Separation of caffeine and catechins from tea extracts usually requires conventional liquid-liquid extraction employing chloroform. This work was planned to improve a green extraction technique to distunguish these important chemicals from green tea. Extraction of caffeine and catechins from Turkish green tea firstly employing MAE, and then to separate these compounds from each other using a SFE method were purpose of this study. Microwave assisted extraction was applied to extract tea components from green te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Recently, aqueous ethanol, acetone, and ethyl acetate were compared to extract green tea polycatechins, and it was found that acetonic extract of green tea possesses maximum extraction of polyphenols, i.e., 1,325.81 ± 64.85 mg GAE/100 g followed by ethanol and ethyl acetate as viewed in the current study (Ashfaq et al, 2019). Another group of researchers mentioned that catechins in supercritical fluid extract of green tea were 60.56 mg/g at 2,900 psi and 60°C (Serdar et al, 2019). Moreover, purity of EGCG in total polyphenol content of green tea was in the range of 70.7% to 76.5% at varied temperature, pressure, pH, and flow rate-like conditions (Mondal & De, 2018).…”
Section: Hplc Quantification Of Egcg In Green Tea Extractsmentioning
confidence: 58%
“…Recently, aqueous ethanol, acetone, and ethyl acetate were compared to extract green tea polycatechins, and it was found that acetonic extract of green tea possesses maximum extraction of polyphenols, i.e., 1,325.81 ± 64.85 mg GAE/100 g followed by ethanol and ethyl acetate as viewed in the current study (Ashfaq et al, 2019). Another group of researchers mentioned that catechins in supercritical fluid extract of green tea were 60.56 mg/g at 2,900 psi and 60°C (Serdar et al, 2019). Moreover, purity of EGCG in total polyphenol content of green tea was in the range of 70.7% to 76.5% at varied temperature, pressure, pH, and flow rate-like conditions (Mondal & De, 2018).…”
Section: Hplc Quantification Of Egcg In Green Tea Extractsmentioning
confidence: 58%
“…In green tea samples worked upon, catechins were present in the order of amount as epigallocatechin > epigallocatechin gallate > epicatechin > catechin. Among 10, 20, 25 and 30 MPa tested, 25 MPa provided highest yield [36]. This indicates that regulated pressure plays a role in extraction efficiency, and not only a ramp.…”
Section: Extraction Of Catechin By Sfementioning
confidence: 81%
“…Similar sequential extraction has been conducted by Serdar et al wherein optimized separation conditions were 60 °C, 250 MPa, 180 min, ethanol as modifier at 0.5 mL min -1 flow rate from Turkish green tea sample. The total run time was 3 h for caffeine and 3 h for catechin, i.e., in total 6 h for complete catechin extraction, per double run (direct method) [36]. These authors however contemplated using microwave treatment first, since it is way briefer than SC-CO 2 in process time, and the mixed yield could be separated post extraction by SFE.…”
Section: Extraction Of Catechin By Sfementioning
confidence: 99%